Investigation of cerebral iron deposition in aged patients with ischemic cerebrovascular disease using susceptibility-weighted imaging - Liu Y; Liu J; Liu H; Liao Y; Cao L; Ye B; Wang W (Therapeutics and Clinical Risk Management, 2016)
Yin Liu, Jun Liu, Huanghui Liu, Yunjie Liao, Lu Cao, Bin Ye, Wei Wang Department of Radiology, The Third Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China Objective: The aim of this study was to investigate focal iron deposition level in the brain in patients with ischemic cerebrovascular disease and its correlation with cerebral small vessel disease imaging markers.Patients and methods: Seventy-four patients with first-ever transient ischemic attack (median age: 69 years; 30 males and 44 females) and 77 patients with positive ischemic stroke history (median age: 72 years; 43 males and 34 females) were studied retrospectively. On phase image of susceptibility-weighted imaging and regions of interest were manually drawn at the bilateral head of the caudate nucleus, lenticular nucleus (LN), thalamus (TH), frontal white matter, and occipital white matter. The correlation between iron deposition level and the clinical and imaging variables was also investigated.Results: Iron deposition level at LN was significantly higher in patients with previous stroke history. It linearly correlated with the presence and number of cerebral microbleeds (CMBs) but not with white matter hyperintensity and lacunar infarct. Multiple linear regression analysis showed that deep structure CMBs were the most relevant in terms of iron deposition at LN.Conclusion: Iron deposition at LN may increase in cases of more severe ischemia in aged patients with transient ischemic attack, and it may be an imaging marker for CMB of ischemic origin. Keywords: cerebral microbleed, ischemia, susceptibility-weighted imaging, iron, lenticular nucleus